Black Light, White Revolution: Translation, Adaptation, and Appropriation in Galway Kinnell's Cold War Writings on Iran. (2nd October 2015) - Motlagh, Amy
Abstract : In 1959, the American poet Galway Kinnell won a Fulbright fellowship to live and teach for a year in Iran. Although he did not learn more than '500 or so words' of Persian during his stay, he acknowledged the impact his fellowship year had on him, and set his only novel, Black Light (1966. Boston, MA: Houghton Mifflin), in Iran. In story and content, Black Light is almost certainly an imitation of Sadeq Hedayat's The Blind Owl (1957. New York: John Calder), although the poet has no memory of reading Hedayat's masterwork, and indeed maintains that he never read it at all. The history of American practices of translation assumes new significance when considering the products of Kinnell's time in Iran. This essay focuses on Black Light and Kinnell's ethnographic travel writing, which appeared under the title 'Persian Journals' in a series in the Tehran Journal magazine, arguing that each of these texts is a translation into an American idiom of the different encounters Kinnell was having with Iran.